Ionic Covalent Organic Frameworks: Design of a Charged Interface Aligned on 1D Channel Walls and Its Unusual Electrostatic Functions - Huang, Ning; Wang, Ping; Addicoat, Matthew A.; Heine, Thomas; Jiang, Donglin (Angewandte Chemie International Edition, 2017)
Covalent organic frameworks (COFs) have emerged as a tailor‐made platform for designing layered two‐dimensional polymers. However, most of them are obtained as neutral porous materials. Here, we report the construction of ionic crystalline porous COFs with positively charged walls that enable the creation of well aligned yet spatially confined ionic interface. The unconventional reversed AA‐stacking mode alternately orientates the cationic centers to both sides of the walls; the ionic interface endows COFs with unusual electrostatic functions. Because all of the walls are decorated with electric dipoles, the uptake of CO2 is enhanced by three fold compared to the neutral analog. By virtue of sufficient open space between cations, the ionic interface exhibits exceptional accessibility, efficiency, and selectivity in ion exchange to trap anionic pollutants. These findings suggest that construction of the ionic interface of COFs offers a new way to structural and functional designs. A scaffold for ionic interfaces: Covalent organic frameworks were synthesized. They bear ionic interfaces that are well aligned and spatially confined on the one‐dimensional channel walls. The ionic interfaces exert profound effects on the frameworks and trigger unusual electrostatic functions, such as the adsorption of CO2 and the selective removal of anionic pollutants.